Pengaruh Personal Networks dan Kualitas Produk Terhadap Keunggulan Bersaing UMKM melalui Strategi Pemasaran Digital sebagai Pemoderasi: The Influence of Personal Networks and Product Quality on the Competitive Advantage of MSMEs through Digital Marketing Strategy as a Moderator - Wicaksono, Baghas Budi; Audinasari, Rifka; Mindayani, Raidha (Jurnal Riset Ilmu Ekonomi, 2023)
This research aims to identify the influence of personal network variables and product quality on the competitive advantage of MSMEs through moderating variables. The data used in this research is primary data in the form of a questionnaire filled in by 167 respondents who have heterogeneity in gender, age, education and information about business. Researchers use Structural Equation Modeling as a method for extracting data. The research results show that all independent and moderating variables have a positive influence on the competitive advantage variable of MSMEs. This is indicated by a t-statistic value that is greater than the t-table with a p-value < 0.05. The validity and reliability indicators through outer loading also show values ​​above 0.6 on average. Therefore, the implications of this research are as follows: (1) The government as a stakeholder must be able to bridge the community to be able to access business capital through networks and business incubators, (2.) The community must have good literacy regarding the quality of a product so that it can have competitiveness in the free market, (3.) Academics and researchers are expected to accelerate the downstreaming of products so that they have greater benefits for the informal sector economy.